Hubungan Tingkat Pengetahuan dan Sikap dengan Praktik Penggunaan Masker pada Lansia - Prajaningrum, Anindita; Wurjanto, Moh. Arie; Martini, Martini; Sutiningsih, Dwi (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Background: The trend of Covid-19 in Indonesia continues showing positive result, the government then starting to change the status from pandemic to endemic. The Indoensian government made a policy of easing the use of masks for the community not including vulnerable groups like elderly. However, there are elderly who still do not wear masks. The purpose of this study was analyzing the relation between individual characteristics, level of knowledge, and attitudes with the practice of using masks in the elderly in Wonogiri District.Methods: This research is an analytic observational research with a cross sectional study design. The research subjects were 105 elderly respondents from 15 sub-districts in Wonogiri District. The sampling technique is quota sampling. Data collection using questionnaire with interview method. Test data analysis using test chi-square.Result: The outcome of this study show indicate that there is a significant relation between level of knowledge (p=0.001) and attitude (p=0.005) with the practice of using face mask among elderly.Conclusion : It can be concluded that individual, level of knowledge, and attitude are related with the practice of using face mask among elderly. Increased socialization related to the policy of easing masks and educating people on how to use masks properly.